2013
DOI: 10.1104/pp.113.217208
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor-Like Channel3.3 Is Involved in Mediating Glutathione-Triggered Cytosolic Calcium Transients, Transcriptional Changes, and Innate Immunity Responses in Arabidopsis

Abstract: The tripeptide reduced glutathione (GSH; g-glutamate [Glu]-cysteine [Cys]-glycine) is a major endogenous antioxidant in both animal and plant cells. It also functions as a neurotransmitter mediating communication among neurons in the central nervous system of animals through modulating specific ionotropic Glu receptors (GLRs) in the membrane. Little is known about such signaling roles in plant cells. Here, we report that transient rises in cytosolic calcium triggered by exogenous GSH in Arabidopsis (Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 105 publications
(114 reference statements)
3
86
0
Order By: Relevance
“…Since the discovery of GLR genes in plants (Lam et al, 1998), many studies have demonstrated that Ca 2+ levels mediated by AtGLRs affect myriad cellular processes (Kim et al, 2001;Meyerhoff et al, 2005;Cho et al, 2009;Michard et al, 2011;Li et al, 2013;Mousavi et al, 2013;Vincill et al, 2013). To our knowledge, this is the first report demonstrating that cytoplasmic Ca 2+ dynamics modulated by a plant GLR play a pivotal role in seed germination.…”
Section: +mentioning
confidence: 80%
See 1 more Smart Citation
“…Since the discovery of GLR genes in plants (Lam et al, 1998), many studies have demonstrated that Ca 2+ levels mediated by AtGLRs affect myriad cellular processes (Kim et al, 2001;Meyerhoff et al, 2005;Cho et al, 2009;Michard et al, 2011;Li et al, 2013;Mousavi et al, 2013;Vincill et al, 2013). To our knowledge, this is the first report demonstrating that cytoplasmic Ca 2+ dynamics modulated by a plant GLR play a pivotal role in seed germination.…”
Section: +mentioning
confidence: 80%
“…In plants, several gene families are thought to encode Ca 2+ -permeable channels (Ward et al, 2009;Hedrich, 2012), among them Arabidopsis (Arabidopsis thaliana) glutamate receptor homologs (AtGLRs) share high structural similarity to ionotropic Glu receptor Ca 2+ channels in animals (Lam et al, 1998), and consist of 20 gene family members (Lacombe et al, 2001). Studies have shown that these plant GLRs participate in diverse physiological and developmental procedures, including pollen tube morphogenesis (Michard et al, 2011), root development (Kang et al, 2004;Li et al, 2006;Vincill et al, 2013), stomatal closure regulation (Cho et al, 2009), and various stress responses (Kim et al, 2001;Meyerhoff et al, 2005;Li et al, 2013;Mousavi et al, 2013), which are mostly dependent on Ca 2+ . Despite the importance of AtGLR-related Ca 2+ modulation in these processes, the function and molecular mechanism of Ca 2+ signaling and AtGLRs in seed germination, the early plant developmental event that greatly impacts the plant's entire life and agricultural performance (Rajjou et al, 2012), is largely unknown.…”
mentioning
confidence: 99%
“…ILK1's kinase-independent role in promoting rapid flg22-induced PM depolarization may be due to the interaction between transport systems. For example, HAK5 transport could be influencing other channels at the PM such as the Glu receptor-like channel GLR3.3, which promotes Ca 2+ influx during immunity (Qi et al, 2006;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…16 The predicted membrane topology and orientation of the protein as a tetramer, with the ATD and LBD exposed to the external side of the membrane, are considered to be conserved in plant GLRs. 17 Understanding the function of plant GLRs has previously been hampered by gene redundancy and toxicity although genetic, pharmacological, and electrophysiological approaches suggested diverse physiological roles such as carbon/nitrogen balance regulation, 18,19 stomatal opening, 20 pollen tube growth, 21 plant-pathogen interaction, [22][23][24] responses to wound, 25,26 and lateral root formation. 12 Recently, 2 of the Arabidopsis GLRs, AtGLR3.4 and 1.4, were shown to function as amino acid gated channels when expressed in heterologous systems, 13,27 further confirming the functional commonality of plant and mammalian glutamate receptors.…”
Section: Introductionmentioning
confidence: 99%